Looking into laminin receptor: critical discussion regarding the non-integrin 37/67-kDa laminin receptor/RPSA protein - DiGiacomo, Vincent (Biol Rev Camb Philos Soc, 2015)
The 37/67-kDa laminin receptor (LAMR/RPSA) was originally identified as a 67-kDa binding protein for laminin, an extracellular matrix glycoprotein that provides cellular adhesion to the basement membrane. LAMR has evolutionary origins, however, as a 37-kDa RPS2 family ribosomal component. Expressed in all domains of life, RPS2 proteins have been shown to have remarkably diverse physiological roles that vary across species. Contributing to laminin binding, ribosome biogenesis, cytoskeletal organization, and nuclear functions, this protein governs critical cellular processes including growth, survival, migration, protein synthesis, development, and differentiation. Unsurprisingly given its purview, LAMR has been associated with metastatic cancer, neurodegenerative disease and developmental abnormalities. Functioning in a receptor capacity, this protein also confers susceptibility to bacterial and viral infection. LAMR is clearly a molecule of consequence in human disease, directly mediating pathological events that make it a prime target for therapeutic interventions. Despite decades of research, there are still a large number of open questions regarding the cellular biology of LAMR, the nature of its ability to bind laminin, the function of its intrinsically disordered C-terminal region and its conversion from 37 to 67 kDa. This review attempts to convey an in-depth description of the complexity surrounding this multifaceted protein across functional, structural and pathological aspects.